Media Vs. Law: Which Acts as a Tool of Social Engineering? - Hamdani, Fathul; Fauzia, Ana; Mardhiyana, Rezka; Kusuma, Lalu Aria Nata (Indonesia Media Law Review, 2023)
According to Roscoe Pound, law is viewed as a tool for social engineering. However, the situation in Indonesia reveals that the law has not effectively fulfilled its role as a tool for social engineering and development, as envisioned by Mochtar Kusumaatmadja. This is evident in various law enforcement cases in Indonesia, where the process tends to be sluggish and only gains attention after it becomes viral in the mass media. This study aims to explore the underlying factors behind the influence of mass media on law enforcement in Indonesia and investigate whether both the media and the law can function as tools for social engineering simultaneously. The article adopts a normative legal research methodology, utilizing statutory, conceptual, and case-based approaches. The research findings demonstrate that while the mass media has a positive impact, there are still areas for improvement within the Indonesian legal system, particularly concerning the suboptimal performance of law enforcement officials and state authorities. Despite the potential for mutual support between the media and the law, the current scenario highlights the need for the media to serve as an information disseminator, supervisor, social control, and shaper of public opinion, while the coercive nature of the law can exert pressure on law enforcers and government officials to fulfill their duties and responsibilities.